Parental health beliefs, intention, and strategies about COVID-19 vaccine for their children: A cross-sectional analysis from five Arab countries in the Middle East - Mohammed, Ali Haider; Hassan, Bassam Abdul Rasool; Wayyes, Abdulrasool M.; Gadhban, Ansam Qassim; Blebil, Ali; Abu Alhija, Sara; Darwish, Rula M.; Al-Zaabi, Ahmed Talib; Othman, Gamil; Jaber, Ammar Ali Saleh; Al Shouli, Betoul Ahmad; Dujaili, Juman; et al. (Elsevier, 2022)
Background The issue around vaccination of children has brought divergent opinions among the populations across the globe and among the Arab population. There has been a low response rate to the calls for vaccination of children and this is reflective of the sentiments which parents may have towards their children being vaccinated. This study aims to explore the parents health beliefs, intentions, and strategies towards the COVID-19 vaccine for their children among Arab population. Methods A cross-sectional study using an online survey from October to December 2021, was carried out in five Arab countries in the Middle East. A reliable health belief model (HBM) including five domains: severity, susceptibility, benefits, barriers and cues to action, was adopted. Chi-square, Mann-Whitney test, and multivariable logistic regression were performed for data analysis. Results The survey response rate was 58 % (1154/2000). Only 56 % of Arab parents are intended to vaccinate their children against COVID-19. The mean scores of parental health belief are largely driven by their concern over the vaccines side effect (p = 0.001) followed by its efficacy, safety (p < 0.001), and scheduling difficulty (p = 0.029). However, strategies that were statistically encouraged parents to vaccinate their children included doctors recommendation, adequate information being provided, and acceptance of the vaccine by public (p < 0.001). Parents with one child were almost three times most likely to vaccinate their children (OR = 2.660, 95 %CI = 1.572-4.504, p < 0.001). Parents' desire to vaccinate their children is also influenced by other factors such as job loss owing to COVID-19 and the presence of a health worker in the family. Conclusion Intention of Arab parents to vaccinate their children via COVID-19 vaccine is still limited. Thus, it is essential for health care authorities to avail the information which will debunk the erroneous beliefs which some parents have developed towards the vaccination of children against COVID-19.